2019
DOI: 10.4028/www.scientific.net/msf.963.722
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysical and Optical Properties of 4H-SiC UV Detectors Irradiated with Electrons

Abstract: Comparative studies of the structural, electrophysical properties and spectral sensitivity of 4H-SiC photodetectors of ultraviolet radiation in the spectral range of 200-400 nm were carried out before and after electron irradiations. Photodetectors with Cr Schottky barriers with thickness of 20 nm and 8 mm diameter were formed on n-4H-SiC CVD epitaxial layers with a thickness of 5 μm and concentration Nd-Na= (1-4) х1014 cm-3. Cr/4H-SiC photodiodes were irradiated by electrons at 0.9 MeV energy with doses (0.2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…prepared SiC MSM‐PDs by CVD method, the PDs showed less than 10 −10 A dark current at −10 V after irradiated with 0.9 MeV electrons. [ 105 ] In the same year, they irradiated the PDs with 15 MeV protons, and found that there is no change in the photosensitivity of PDs. [ 106 ] In 2020, they studied the effect of temperature on the performance of SiC MSM‐PDs with 15 MeV protons irradiation, they found that the PDs have an increased QE under 200 °C than 25 °C, which can be attributed to an increase in the lifetime of minority carriers upon heating.…”
Section: Research Status Of Msm‐pdsmentioning
confidence: 99%
“…prepared SiC MSM‐PDs by CVD method, the PDs showed less than 10 −10 A dark current at −10 V after irradiated with 0.9 MeV electrons. [ 105 ] In the same year, they irradiated the PDs with 15 MeV protons, and found that there is no change in the photosensitivity of PDs. [ 106 ] In 2020, they studied the effect of temperature on the performance of SiC MSM‐PDs with 15 MeV protons irradiation, they found that the PDs have an increased QE under 200 °C than 25 °C, which can be attributed to an increase in the lifetime of minority carriers upon heating.…”
Section: Research Status Of Msm‐pdsmentioning
confidence: 99%
“…Recently, a full evaluation of the research development for the aforesaid MSM-PDs (covering the fundamental structures and materials type, manufacturing processes, operating wavelengths, and performance characteristics) was presented in Refs. [16,18,[62][63][64][65][66][67][68][69][70][71]. On the These two Schottky electrodes are routinely interconnected in a comb configuration in an MSM-PD, leaving a free semiconductor surface between the two contacts that produce and form the active zone in which the light will be caught.…”
Section: Basic Structures Of Msm-pds and Nano-grating Structuresmentioning
confidence: 99%
“…Recently, a full evaluation of the research development for the aforesaid MSM-PDs (covering the fundamental structures and materials type, manufacturing processes, operating wavelengths, and performance characteristics) was presented in Refs. [16,18,[62][63][64][65][66][67][68][69][70][71]. On the other hand, the choice of substrate materials is exclusively reliant on the kind of application and the wavelength-dependent responses that are required for the particular application.…”
Section: Basic Structures Of Msm-pds and Nano-grating Structuresmentioning
confidence: 99%
“…high-power and high temperature electronics as well as harsh environments [4][5][6][7][8][9][10][11]. Specifically, the most used polytype is the 4H-SiC featuring the highest bandgap value of 3.3 eV.…”
Section: Introductionmentioning
confidence: 99%